The Basel II Accord: Internal ratings and bank defferentiation - Eberhard Fees; Ulrich Hege (Goethe University Frankfurt, Center for Financial Studies (CFS), 2004)
The Basel Committee plans to differentiate risk-adjusted capital requirements between banks regulated under the internal ratings based (IRB) approach and banks under the standard approach. We investigate the consequences for the lending capacity and the failure risk of banks in a model with endogenous interest rates. The optimal regulatory response depends on the banks' inclination to increase their portfolio risk. If IRB-banks are well-capitalized or gain little from taking risks, then they will increase their market share and hold safe portfolios. As risk-taking incentives become more important, the optimal portfolio size of banks adopting intern rating systems will be increasingly constrained, and ultimately they may lose market share relative to banks using the standard approach. The regulator has only limited options to avoid the excessive adoption of internal rating systems.
urn:nbn:de:hebis:30-10769
Keywords: K13; H41; 330; Basel II Accord; risk-based capital; internal ratings based approach; bank capital; bank competition; risk-taking